Consulting report – Confecciones Juliett - Garcia Cabello, Gonzalo Asuncion (2019)
In recent years, Peru has experienced a higher average growth higher than other South American countries. This growth can in part be attributed to the Peruvian textile industry, which is one of the strongest manufacturing economies in the country due to its enormous impact on the economy. The growth of the GDP per capita has resulted in a higher spending capacity among Peruvian citizens, and Peruvian consumers are now willing to invest a larger part of their income in clothing. This economic growth has also produced changes in their purchasing processes and increased their expectations for high-quality products. Additionally, Peru ranks fourth in entrepreneurship in Latin America, behind Colombia, Chile, and Ecuador. This emerging entrepreneurial dynamism, however, is a figure of small businesses that are contradicted when compared with the high failure rate. Confecciones Juliett is a Peruvian small business that specializes in the design, manufacturing, and selling of clothing garments for women. After analyzing the internal and external environment of the industry, the organization is facing typical challenges that many Peruvian SMEs encounter in their operations. In sum, the goal of this paper is to define the best and appropriate cost structure for the company, Confecciones Juliett, in order to strengthen their organizational decision making.